Influence of Miombo woodlands management, drivers on land use/cover and forest change, woody composition/diversity, population structure in Malawi - Chirwa, Paxie W. (University of Pretoria, 2020)
Thesis (PhD (Forest Science))--University of Pretoria, 2020.